Pengaruh Komunikasi Interpersonal Terhadap Pelayanan Akademik Mahasiswa - Pratiwi, Resty Mustika; Suseno, Novie Susanti; Muchtar, Alyya Najla (Universitas Garut, 2024)
Abstract The university, as a higher education institution, has the responsibility to develop science and technology and to form a social enlightenment in students to be able to analyze, develop opinions, and enhance critical and reflective knowledge. The primary goal is to create students who can make a positive contribution as the successor generation of the nation. Evaluation of the quality of academic services and interpersonal communication at the Faculty of Communication and Information focuses on factors such as ease, accessibility, speed, reliability, and hospitality in the attitude of service. The research focuses on the quality of academic services, student satisfaction, and their impact on the Faculty of Communication and Information. The method used in this research is a descriptive study method with a quantitative approach. Data analysis techniques in this study are using primary data and secondary data. The data collection technique used is a questionnaire with a total population of 1139 active students in the Faculty of Communication and Information. The sampling technique used was Probabilitiy Sampling with a total of 91 criteria respondents. Research results show that interpersonal communication is categorized on the criterion of